La medicina achuar y su aplicación en la escuela primaria de la comunidad Kaiptach. - Sumpa Kashijint, Najuir María (2009)
Alternative medicine herbal Achuar. Achuar medicinal plants. Rites and myths with respect to medicine. Importance: desvetajas advantages and natural alternative medicine. Application of community medicine at the Kaiptach